Multimorbidity and functional limitation: the role of social relationships. (January 2021) - Jiao, Dandan; Watanabe, Kumi; Sawada, Yuko; Tanaka, Emiko; Watanabe, Taeko; Tomisaki, Etsuko; Ito, Sumio; Okumura, Rika; Kawasaki, Yuriko; Anme, Tokie
Highlights: Multimorbidity is related to a high risk of functional limitation. Rich social relationships may change that association. Facilitating social relationships is essential among older people. Doing so is beneficial for multimorbidity management. Abstract: Objectives: To examine the relationship between multimorbidity and functional limitation, and how social relationships alter that association. Methods: This cross-sectional study used data collected by self-reported questionnaires from adults aged 65 years and older living in a rural area in Japan in 2017. This analysis included complete data from 570 residents. Multimorbidity status was defined as having two chronic diseases exist simultaneously in one individual, and the function status was measured by their long-term care needs. Social relationships were assessed by the Index of Social Interaction and divided into high and low levels. Multiple logistic regression analysis was used to examine the association between social relationships and functional limitation and to assess the role of social relationships in this association. Results: The logistic regression model indicated that the risk of functional limitation was higher in multimorbidity participants than free-of-multimorbidity participants (OR = 2.55, 95% CI = 1.56–4.16). Compared with participants with no multimorbidity and a high level of social relationships, low level of social relationships increased the risk of functional limitation among participants both with and without multimorbidity, with the OR = 7.71, 95% CI = 3.03–19.69 and OR = 3.28, 95% CI = 1.30–8.27, respectively. However, no significant result was found in participants with multimorbidity and a high level of social relationships ( P = 0.365). Conclusions: Multimorbidity was associated with functional limitations. However, this association could be increased by a low level of social relationships and decreased by a high level of social relationships.